Digitally Patterned Mesoporous Carbon Nanostructures of Colorless Polyimide for Transparent and Flexible Micro-Supercapacitor - Hyeonwoo Kim; Suwon Hwang; Taeseung Hwang; Jung Bin In; Junyeob Yeo (Energies, 2021)
Here, we demonstrate the fabrication of a flexible and transparent micro-supercapacitor (MSC), using colorless polyimide (CPI) via a direct laser writing carbonization (DLWC) process. The focused laser beam directly carbonizes the CPI substrate and generates a porous carbon structure on the surface of the CPI substrate. Fluorine, which is one of the chemical compositions of CPI, can enhance the specific area and the conductivity of the carbon electrode by creating micropores in carbon structures during carbonization. Thus, the fabricated carbonized CPI-based MSC shows enhanced specific capacitance (1.20 mF at 10 mV s−1) and better transmittance (44.9%) compared to the conventional PI-based MSC. Additionally, the fabricated carbonized CPI-based MSC shows excellent cyclic performance with minimal reduction (<~10%) in 3000 cycles and high capacitance retention under mechanical bending test conditions. Due to its high flexibility, transparency, and capacitance, we expect that carbonized CPI-based MSC can be further applied to various flexible and transparent applications.